2011
DOI: 10.1109/tns.2010.2093909
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Real Time FPGA-Based Three Dimensional Positioning Algorithm

Abstract: We report on the implementation and hardware platform of a real time Statistics-Based Positioning (SBP) method with depth of interaction processing for a positron emission tomography detector. The processing method works in conjunction with continuous miniature crystal element (cMiCE) detectors using a sensor on the entrance surface design. Our group previously reported on a Field Programmable Gate Array (FPGA) SBP implementation that provided a two dimensional (2D) detector positioning solution [1]. This new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 15 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…To address both of these issues we are currently designing a high-throughput data acquisition electronics board [30]. We have implemented both 2D and 3D SBP algorithms in our FPGA [31,32]. The 2D SBP implementation runs at over 360 KHz and the 3D SBP implementation runs at over 220 KHz.…”
Section: Discussionmentioning
confidence: 99%
“…To address both of these issues we are currently designing a high-throughput data acquisition electronics board [30]. We have implemented both 2D and 3D SBP algorithms in our FPGA [31,32]. The 2D SBP implementation runs at over 360 KHz and the 3D SBP implementation runs at over 220 KHz.…”
Section: Discussionmentioning
confidence: 99%
“…We will also integrate this readout electronics to the acquisition board under development in our lab [11,12]. …”
Section: Discussionmentioning
confidence: 99%
“…3D SBP not only provides the DOl information but also improves the 2D positioning performance as well, especially at the edge and comer areas [8] [9]. Meanwhile, the real-time realization of the 3D positioning algorithm on FPGA was also carried out and reported [9]. All of these research efforts have shown that the SBP algorithm has a very good application prospect for continuous crystal based PET detectors.…”
Section: Introductionmentioning
confidence: 99%
“…By creating a 2D-LUT for different DOl (depth of interaction) region, for example, 15 DOl regions in [8], a 3D-LUT is built to directly estimate 3D coordinates in the detector. 3D SBP not only provides the DOl information but also improves the 2D positioning performance as well, especially at the edge and comer areas [8] [9]. Meanwhile, the real-time realization of the 3D positioning algorithm on FPGA was also carried out and reported [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation